2022
DOI: 10.1039/d2ce00491g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal formation of bismuth-titanate nanoplatelets and nanowires: the role of metastable polymorphs

Abstract: Understanding the processes involved in the formation of nanoparticles is a prerequisite for the control of their morphology. In this investigation we reveal the processes leading to the formation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…BIT can be successfully synthesized with the hydrothermal treatment of an aqueous suspension of precipitated Bi 3+ and Ti 4+ ions in mineralizer hydroxide (NaOH or KOH) with a moderate concentration. 27,28,[30][31][32][50][51][52][53] The synthesized BIT nanoparticles appear in a wide variety of different nano-morphologies, including 2-D platelet crystals, (i.e., rectangular nanoplatelets and nanosheets), 27,28,32,50,52,53 1-D crystals (e.g., nanowires, nanobelts, nanobundles, nanorods), 27,28,[51][52][53] and 3-D nanostructures assembled from 1-D or 2-D nanoparticles. 30,31,51 Our research showed that the morphologies of the product particles crucially depend on the concentration of the mineralizer hydroxide.…”
Section: Hydrothermal Synthesis Of Bismuth-titanate Nanoplatelets And...mentioning
confidence: 99%
See 4 more Smart Citations
“…BIT can be successfully synthesized with the hydrothermal treatment of an aqueous suspension of precipitated Bi 3+ and Ti 4+ ions in mineralizer hydroxide (NaOH or KOH) with a moderate concentration. 27,28,[30][31][32][50][51][52][53] The synthesized BIT nanoparticles appear in a wide variety of different nano-morphologies, including 2-D platelet crystals, (i.e., rectangular nanoplatelets and nanosheets), 27,28,32,50,52,53 1-D crystals (e.g., nanowires, nanobelts, nanobundles, nanorods), 27,28,[51][52][53] and 3-D nanostructures assembled from 1-D or 2-D nanoparticles. 30,31,51 Our research showed that the morphologies of the product particles crucially depend on the concentration of the mineralizer hydroxide.…”
Section: Hydrothermal Synthesis Of Bismuth-titanate Nanoplatelets And...mentioning
confidence: 99%
“…30,31,51 Our research showed that the morphologies of the product particles crucially depend on the concentration of the mineralizer hydroxide. 52 The nanowires (NWs) formed when the precipitated ions were hydrothermally treated in aqueous solutions of NaOH with lower concentrations, whereas the nanoplatelets (NPLs) were obtained at higher NaOH concentrations. For example, the hydrothermal treatment for 38 hours at 200 °C produced NWs (from 15 nm to 35 nm wide and from several hundreds of nm to several µm long) in 0.5 mol/L NaOH, whereas the rectangular NPLs (approximately 10 nm thick and from 50 nm to 200 nm wide) were synthesized in 2-mol/L NaOH (Figure 6 (a) and (b)).…”
Section: Hydrothermal Synthesis Of Bismuth-titanate Nanoplatelets And...mentioning
confidence: 99%
See 3 more Smart Citations